2012
DOI: 10.1038/ejhg.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal microarray analysis as a first-line test in pregnancies with a priori low risk for the detection of submicroscopic chromosomal abnormalities

Abstract: In this study, we aimed to explore the utility of chromosomal microarray analysis (CMA) in groups of pregnancies with a priori low risk for detection of submicroscopic chromosome abnormalities, usually not considered an indication for testing, in order to assess whether CMA improves the detection rate of prenatal chromosomal aberrations. A total of 3000 prenatal samples were processed in parallel using both whole-genome CMA and conventional karyotyping. The indications for prenatal testing included: advanced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 45 publications
(94 reference statements)
4
105
2
Order By: Relevance
“…The frequency of UDs in our cohort matches the frequency of pathogenic submicroscopic array findings in pregnancies without ultrasound abnormalities after excluding SL for neurodevelopmental diseases published in the literature. 7,9,28,29 Thus our results support the hypothesis that there is a background risk of~0.5% for a clinically relevant submicroscopic chromosome abnormality (exclusive SL) in the general population. 30 In our opinion, UDs found in our cohort are of additional value in routine prenatal genomic array testing as most (4/5) of them lead to (possibly) severe (including intellectual disability and/or a reduced life expectancy) early-onset diseases, which can be missed by ultrasound examination.…”
Section: Rarity Of Particular Imbalances and Postnatal Biassupporting
confidence: 85%
“…The frequency of UDs in our cohort matches the frequency of pathogenic submicroscopic array findings in pregnancies without ultrasound abnormalities after excluding SL for neurodevelopmental diseases published in the literature. 7,9,28,29 Thus our results support the hypothesis that there is a background risk of~0.5% for a clinically relevant submicroscopic chromosome abnormality (exclusive SL) in the general population. 30 In our opinion, UDs found in our cohort are of additional value in routine prenatal genomic array testing as most (4/5) of them lead to (possibly) severe (including intellectual disability and/or a reduced life expectancy) early-onset diseases, which can be missed by ultrasound examination.…”
Section: Rarity Of Particular Imbalances and Postnatal Biassupporting
confidence: 85%
“…12 The results suggest that fetal anomalies on ultrasonography would be expected to be rare, consistent with the low prevalence of 15q13.3 deletions detected by prenatal chromosomal microarray studies. 11,23,24 Postnatal chromosomal microarray detection, perhaps secondary to referral for DD/ID, is higher. 9 By contrast, the most common large rare CNVs, 22q11.2 deletions, have high penetrance for both neuropsychiatric disorders and congenital anomalies, 25 and higher prenatal detection (0.29%) as compared with 15q13.3 deletions (0.02-0.09%).…”
Section: 5 Discussionmentioning
confidence: 99%
“…Chromosomal microarray analysis may soon become the standard of care in the prenatal setting (1,2). Not discussed is the potential for later-onset phenotypes of findings identified in utero and the resultant ethical and societal challenges.…”
Section: To the Editormentioning
confidence: 99%
“…Recent studies (1,2) have demonstrated the advantages of genome-wide chromosomal microarray analysis over karyotype for the prenatal detection of pathogenic copy number variants. Chromosomal microarray analysis may soon become the standard of care in the prenatal setting (1,2).…”
Section: To the Editormentioning
confidence: 99%